Teknologi Budidaya Ikan Badut Amphiprion Sp. Di Balai Besar Perikanan Budidaya Laut (Bbpbl), Lampung - Andri Iskandar; Muhamad Erlan Hafid Djunaedi; Muhammad Arif Mulya; Dian Eka Ramadhani; Nazla Wafi; Yuli Yulianti (Universitas Mataram, 2024)
Clownfish Amphiprion sp., have a relatively wide distribution area, especially in Indo-Pacific waters. In nature these fish live in small groups in one anemone and consist of one pair of parents, the others are usually smaller in size which are still in the male sex. If one of the parent pairs dies, the position will be replaced by the largest in the group, especially the female. This condition is usually called sequential hermaphrodite. The purpose of this study was to gather information on the techniques for fish hatchery clownfish to produce quality fish. Clownfish spawn with a sex ratio of 1:1, with an average spawning frequency of 2 times a month. Clown fish can produce eggs with an average of 419 eggs, fertilization rate (FR) 76,37%, hatching rate (HR) 75,27%, and survival rate (SR) 58,35%. For one year, the total number of fish hatchery that can be produced is 108.911. Payback period of 8,2 years, break event point (unit) of 73.859 fish/year, break event point (rupiah) of Rp. 369.292.918, and cost of production of Rp. 3.817/fish